Influence of Integrated Nutrient and Weed Management on Growth, Yield and Quality of Soybean - Apon, M.; Nongmaithem, D. (International Journal of Bio-resource and Stress Management, 2022)
A study was carried out at the experimental farm of School of Agricultural Sciences and Rural Development, Nagaland University, Medziphema campus, dist. Nagaland, India during the Kharif season (June to October) of 2017 and 2018 to assess the influence of integrated nutrient and weed management on soybean growth, yield and quality. The split-plot design was used with three replications: three nutrient management treatments and five weed management treatments in the main-plot and sub-plot, respectively. The pooled results revealed that the application of 50% RDF+50% organic through Rhizobium+Phosphate Solubilising Bacteria recorded significantly lower weed density and weed dry weight. Plant height (46.12 cm), plant dry matter (10.00 g plant-1), number of pods plant-1 (53.97), seed yield (16.28 q ha-1), straw yield (22.69 q ha-1), oil content (18.70%) and protein content (38.10%) were recorded highest under 75% RDF+25% organic through FYM+Phosphate Solubilising Bacteria. All of the weed treatments recorded lower weed density and dry weight over the weedy check significantly. Weed free treatment (hand weeding at 15, 30 and 45 DAS) gave highest seed yield (20.67 q ha-1) and straw yield (26.28 q ha-1). It was followed by propaquizafop @ 0.075 kg a.i. ha-1+hand weeding at 45 DAS and pendimethalin @ 1 kg a.i. ha-1+hand weeding at 30 DAS. Weed free registered highest oil content (19.38%) and protein content (38.97%) which was statistically at par with propaquizafop @ 0.075 kg a.i. ha-1+hand weeding at 45 DAS and pendimethalin @ 1 kg a.i. ha-1+hand weeding at 30 DAS.